Case study of flood disaster relief shelters at Kampung Laloh and Kampung Karangan, Kelantan, Malaysia - Ebaid, Tamara A.A (2018)
Though floods are considered an annual disaster in Kelantan, the record-setting flood of 2014/2015 caused a widespread flooding in different Malaysian states, causing one of the most devastating flood disasters recorded in history. While the disaster itself is traumatic, the experience of evacuation and shelter provision can be extremely challenging. Due to the country’s high-risk and repetitive flood disaster occurrence, an implementation of a well-equipped disaster relief shelter is vital for the victims. It is one of the most crucial and immediate needs for victims, which continues for a long period of time after a disaster. A review of the literature, case studies, guidance, and reports relating to the design of disaster relief shelters indicates that their provision and performance are not currently as effective as they could be. The objective of this paper is to review current provision of disaster relief shelters in the 2014/2015 flood disaster in Kelantan, examining the repeated issues and proposing possible solutions for a better disaster relief shelter. The aim of this study is to improve current shelter provision to the victims that experience floods yearly. A case study was conducted on 2 towns in Kelantan, Kampung Laloh and Karangan to explore the disaster relief shelters used, while interviews were conducted with individuals from NGOs that have had a contribution during the floods in Malaysia. Case study data and interviews were analyzed for themes, and comparisons of these themes were made between different sources of information. The problems with current disaster relief shelters were then listed in the form of planning considerations that can be used and applied before the next disaster occurs. The research proposes planning considerations to improve the current shelter approach which will allow for a more efficient response to the next major disaster. The key findings of the research revealed that it is necessary to have the provision of better-quality shelters, and the way forward is implementing new planning consideration. A new approach to the planning consideration, that is, timing to providing these shelter, long term shelter possibilities, evolvement of temporary shelters to permanent housing and lastly preparedness is identified and discussed. All these factors are vital in the post-disaster scenario and are all inter-related with each other. This study will contribute to the knowledge of disaster relief shelters and will offer a guide for other agencies responding to the next disaster to measure their current response in terms of shelter.